PELATIHAN PEMANFAATAN BARANG BEKAS SEBAGAI PRODUK INTERIOR DAN ARSITEKTUR DI KELURAHAN SINRIJALA KOTA MAKASSAR - Amalia, Andi Annisa; Amal, Citra Amalia; Syahriyunita, Andi (Jurnal Balireso: Jurnal Pengabdian pada Masyarakat, 2019)
Recycle goods that are generally regarded as household waste that is no longer useful so thrownaway. whereas with the development of science, especially the field of interior architecture anddesign demands of human needs in their house, these used items can be processed into morevaluable goods. Used goods such as plastic, wood waste, newsprint, sewing machines fashioned,wall clocks scars, cutting boards, kitchen appliances and so on can be recycled and diremodellingby design decopage into interior products more attractive and aesthetically pleasing high aslanterns, ornaments, picture frames , where newspapers, baskets, wall hangings, could even belounge chairs and partitions. But to do that, it takes a creative idea and the ability to process them.To that end, it is expected that this training can develop the capacity of communities using thriftinto interior and architectural products that can boost household economies in Sub Sinrijala.